A Literature Review on the Transformation of Cultural Values under Globalization: A Humanities Perspective - Firayani (Kamara Journal, 2026)
Globalization has significantly reshaped cultural values and identities through the expansion of digital media, migration, transnational markets, and global consumer culture. These transformations influence everyday practices, social norms, and symbolic systems, generating both opportunities for intercultural exchange and tensions related to homogenization and cultural erosion. This study aims to analyze how globalization transforms cultural values and identities and how the humanities interpret and critically respond to these changes. This research employed a qualitative systematic literature review approach, examining peer-reviewed articles published between 2023 and 2025. Data were collected through database searches, screening, and thematic categorization. The analysis was conducted using qualitative content analysis and critical discourse analysis to identify patterns of hybridization, identity negotiation, cultural tension, and ethical reflection within humanities scholarship. The findings indicate that globalization produces hybrid and multilayered identities through selective cultural adaptation rather than simple cultural replacement. While consumer capitalism and Western cultural dominance generate homogenizing pressures, communities actively negotiate global influences within local frameworks. Humanities scholarship provides theoretical models, critical perspectives on power structures, and ethical guidance for cultural sustainability. The study concludes that understanding cultural transformation under globalization requires humanistic reflection capable of interpreting symbolic meaning, identity dynamics, and ethical implications in an interconnected world